1989
DOI: 10.1038/jcbfm.1989.124
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Glutamate Decarboxylase Activity in Substantia Nigra and Caudoputamen following Transient Hyperglycemic Ischemia in the Rat

Abstract: Summary: Glutamate decarboxylase (GAD) activity was determined in caudoputamen (CP), substantia nigra (SN), and cerebral cortex (CCX) after 19-22 h of recirculation following 10 min of transient ischemia in hyperglycemic rats, i.e., under the conditions when previously a pro nounced nerve cell damage was demonstrated in both CP and SN. The present results demonstrate a decrease of GAD activity in SN by 30% and in CP by 22% and no change in CCX. No statistically significant change in GAD activity could be detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
(18 reference statements)
0
2
1
Order By: Relevance
“…Fraham et al (2004) observed no differences in the numbers of GAD mRNA-stained cells in the cortex and hippocampus at 7 and 30 days after focal ischemia. This is in contrast to studies that have showed both ischemiainduced increases and decreases in the cellular steady-state level of striatal and cortical GAD mRNA (Folbergrova et al , 1989; Francis and Pulsinelli, 1982; Fukatsu et al , 2002; Najlerahim et al , 1991; Saji et al , 1994; Salin and Chesselet, 1993). In different animal models of cerebral ischemia, GAD protein was observed to be altered after stroke for days (Kang et al , 2002) or even weeks (Salin and Chesselet, 1993; Yamada et al , 1994).…”
Section: Discussioncontrasting
confidence: 99%
“…Fraham et al (2004) observed no differences in the numbers of GAD mRNA-stained cells in the cortex and hippocampus at 7 and 30 days after focal ischemia. This is in contrast to studies that have showed both ischemiainduced increases and decreases in the cellular steady-state level of striatal and cortical GAD mRNA (Folbergrova et al , 1989; Francis and Pulsinelli, 1982; Fukatsu et al , 2002; Najlerahim et al , 1991; Saji et al , 1994; Salin and Chesselet, 1993). In different animal models of cerebral ischemia, GAD protein was observed to be altered after stroke for days (Kang et al , 2002) or even weeks (Salin and Chesselet, 1993; Yamada et al , 1994).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the damage after ischemia with normoglycemia appears later, after a longer "maturation period" as compared to ischemia with hyperglycemia. Folbergrovfi et al (1989) showed that 10 rain of ischemia under hyper-but not normoglycemic conditions decreased the glutamic acid decarboxylase content in SNPR at 24 hrs of recirculation, indicating a decrease at this time-point in the GABA-ergic input to SNPR following ischemia with hyperglycemia. We therefore suggest that an increased excitatory influence on SNPR favouring the development of late post-ischemic seizures and resulting in SNPR damage following ischemia in hyperglycemic subjects, is to some extent caused by decreased inhibition from caudoputamen.…”
Section: Discussionmentioning
confidence: 97%
“…These phenomena induce metabolic stress, energy failure, ionic imbalance, and ischemic injury. 24 , 25 In severe TBI, cerebral blood flow reduction also occurs due to brain swelling, causing secondary ischemia. Cells in an ischemic environment will die within minutes.…”
Section: Discussionmentioning
confidence: 99%